Effect of Glycine and Citric Acid Fuels on Thermochemical Profiles in ZnO Nanoparticle Combustion Synthesis - Simmi; Dr. Verjesh Kumar Magotra; Dr. Shaveta Thakur (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study explores the effect of fuel type and combustion parameters on the synthesis efficiency and material characteristics of zinc-based nano metal oxides produced via the solution combustion process (SCP). Glycine and citric acid were used as organic fuels to drive redox reactions with zinc nitrate acting as the oxidizer. A systematic evaluation of thermal behavior, combustion kinetics, and fuel-to-oxidizer ratios (Φ) was conducted to assess their influence on combustion temperature, particle morphology. Characterization techniques such as flame analysis, X-ray diffraction (XRD), scanning electron microscopy (SEM), and UV-Visible spectroscopy were employed to investigate crystallinity, particle size distribution, and the overall effectiveness of each fuel. The results demonstrate that the choice of fuel significantly impacts flame temperature and the exothermic nature of the reaction, thereby affecting the structural and morphological attributes of the resulting ZnO nanoparticles. Combustion with glycine resulted in a highly exothermic and rapid reaction, producing finer and more porous particles, whereas citric acid facilitated a slower, more uniform combustion, yielding nanoparticles with more consistent morphology. These findings highlight the pivotal role of fuel chemistry in optimizing material properties and improving energy efficiency in SCP-based nanomaterial synthesis.